The Independent Auditor's Civil Liability – An Overview. - Schultz, Joseph J.; Pany, Kurt (The Accounting Review, 1980)
Court actions in the last decade and a half have resulted in an increasingly complex legal environment for the independent auditor. The ordinary amount of class time available to auditing instructors is too short to cover book-length treatments of this environment. This paper presents and describes a matrix which has proved useful in concisely describing many of the subtleties of the environment.